2008
DOI: 10.1016/j.cell.2007.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Root of miRNA-Mediated Gene Silencing

Abstract: MicroRNAs are approximately 22 nucleotide-long RNAs that silence gene expression posttranscriptionally by binding to the 3' untranslated regions of target mRNAs. Although much is known about their biogenesis and biological functions, the mechanisms allowing miRNAs to silence gene expression in animal cells are still under debate. Here, we discuss current models for miRNA-mediated gene silencing and formulate a hypothesis to reconcile differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
694
0
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 955 publications
(716 citation statements)
references
References 33 publications
(85 reference statements)
8
694
0
14
Order By: Relevance
“…The up-regulation of GW182 is more intriguing, because GW182's exact function is yet to be determined. In Drosophila, Ago1-GW182 complexes are essential for miRNA-mediated silencing (Eulalio et al, 2008b), although how this complex achieves silencing is still debated (Eulalio et al, 2008a;Wu and Belasco, 2008). Tethering of GW182 to target mRNA shows that GW182 may facilitate silencing through a mode that bypasses the requirement for Ago2 (Behm-Ansmant et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of GW182 is more intriguing, because GW182's exact function is yet to be determined. In Drosophila, Ago1-GW182 complexes are essential for miRNA-mediated silencing (Eulalio et al, 2008b), although how this complex achieves silencing is still debated (Eulalio et al, 2008a;Wu and Belasco, 2008). Tethering of GW182 to target mRNA shows that GW182 may facilitate silencing through a mode that bypasses the requirement for Ago2 (Behm-Ansmant et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They control a wide range of biological functions such as cellular proliferation, differentiation and apoptosis (Zhao and Srivastava, 2007;Erson and Petty, 2008;Eulalio et al, 2008). Recent reports showed strong evidence that miRNAs can act as oncogenes or tumor suppressors, having key roles in cancer initiation and progression (Cho, 2007;Tili et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mature miRNAs are produced from sequential processing of primary transcripts via specific RNAses. These 18-to 24-nt-long miRNAs down-regulate protein expression of specific mRNA by either translational inhibition or mRNA degradation [14]. Numerous reports have now shown that miRNAs are differentially expressed in many types of human cancers [15,16].…”
mentioning
confidence: 99%
“…In the RISC complex, the active strand is retained and the passenger strand is selectively degraded. The mature miRNA along with RISC binds to complementary sites in the mRNA transcripts and (typically) downregulates gene expression [14,19]. miRNAs that bind to mRNA targets with imperfect complementarity regulate the target gene at the level of protein translation, while miRNAs that bind to their mRNA targets with perfect complementarity induce degradation [20,21].…”
mentioning
confidence: 99%